EVALUATION OF THE IMPLEMENTATION OF SANITATION AT THE MUARO TEMPLE TOURISM IN 2022 - Arnild Augina Mekarisce; Ogy Meyza Pratama; Zuli Rodhiyah; Fajrina Hidayati; Samsidar (International Journal Of Health Science, 2023)
Public places have the potential to become places for disease transmission and environmental pollution, for example, tourist spots. Muaro Jambi Temple is one of the cultural heritage complexes of the largest Hindu-Buddhist temple complex in Southeast Asia. It is also the most visited tourist spot in Muaro Jambi Regency. This study aims to evaluate the implementation of sanitation at the Muaro Jambi Temple tourist area. The method used in this research is qualitative research with an evaluation approach. There were 8 informants in this study who were taken by purposive sampling. Data collection was carried out by means of in-depth interviews, observation, and document review. Data analysis with content analysis method. The validity test of the research was carried out using the triangulation method. The results showed that the human resources of the Jambi Kecil health center had not met the standards, the cleaning staff or caretakers at the temple were sufficient in quantity but had not been assigned specifically to implement standardization of sanitation for tourist attractions. Funds for the implementation of the program from the Public health center come from BOK, while the tourism management has not prepared funds for implementing sanitation. The facilities and infrastructure of the Public health center are adequate, but the sanitation facilities in the temples are not up to standard. There is no policy that regulates STTU. Examination and assessment of sanitation in the temple had never been done before. When a sanitary inspection was carried out, it was found that the Muaro Jambi temple did not meet health requirements, namely 42.63%. It is hoped that the regional government will make regional regulations regarding the application of STTU and tourism managers will start implementing standardization of sanitation as a necessity. Public places can potentially become places for disease transmission and environmental pollution, for example, tourist spots. Muaro Jambi Temple is one of the cultural heritage complexes of the largest Hindu-Buddhist temple complex in Southeast Asia. It is also the most visited tourist spot in Muaro Jambi Regency.